ZINC AND MANGANESE SORPTION BEHAVIOR BY NATURAL ZEOLITE AND BENTONITE - A.L. Iskander; Khald E.M.; Sheta A.S. (Arab Universities Journal of Agricultural Sciences, 2011)
Understanding the sorption process in natural zeolite and bentonite is necessary for effective utilization of these minerals as nutrient adsorbents and on the other side for controlling release of plant nutrients. This research was undertaken to characterize the ability of natural zeolite and bentonite minerals to adsorb and release zinc and manganese. The potentials for sorption of these ions were evaluated by applying the Langmuir and Freundlich equations. The results showed that Langmuir constant [maximum adsorption (b mmol kg-1)] of both Zn and Mn were for bentonite > zeolite While the [binding strength values (k in L.mmol-1)] for zeolite > bentonite      Zn in case of zeolite showed the lowest desorbed percentage particularly at high levels of sorbed Zn. Only, 74.7 % is readily extractable by DTPA after three successive extractions leaving, 25.3 % Zn retained by the mineral. In case of bentonite, 82.26 % of sorbed Zn is readily extractable by DTPA after three successive extractions leaving, 17.74 % Zn retained by the mineral. In case of Mn, 84.63% of Mn sorbed by zeolite is readily extractable by DTPA after three successive extractions leaving, 15.37% Mn retained by the mineral. In case of bentonite, 89.79 % of adsorbed Mn is readily extractable by DTPA after three successive extractions leaving, 10.21 % Mn retained by the mineral.      This ﬁnding may reﬂect clearly the possibility of using natural zeolite and bentonite as a slow release fertilizer for Zn and Mn and on the other hand preventing soil pollution with heavy metals.